Valuasi Ekonomi Sampah Rumah Tangga di Kelurahan Bobosan Purwokerto Utara Kabupaten Banyumas - Meisha, Arief Refo; Anwar, Nurul; Priyono, Rakhmat (Lingka Ekonomika, 2022)
The waste problem is exacerbated by the waste management system in various regions that still uses the old paradigm which sees waste as something that has no value and must be discarded. The waste management process in Bobosan Village is supported by a Recycling Center (PDU) facility which is managed by a Non-Governmental Organization (NGO) using a new paradigm of waste management system that views waste as a resource that has economic value and can be utilized. The purpose of this study is to estimate the economic value of organic and inorganic household waste in Bobosan Village, also to estimate the economic value of household waste that has not been managed by PDU-KSM Bobosan. Based on the results of calculations using the Total Economic Value method, the results obtained are, within one month there is a volume of organic household waste of 19,408.095 kilograms/month with an economic value of Rp.116,448,570,000, the volume of inorganic household waste is 3,667.44 kilograms/month with an economic value of IDR 27,872,544.00, the volume of household waste that has not been managed or utilized is 12,692,977 kilograms with an economic value of IDR 13,259,823.00. The total economic value of household waste in Bobosan Village within one month in 2021 is Rp. 157,580,937.00.